The adventures of Tom Sawyer - Twain, Mark, 1835-1910 (Vintage classics., 2010)
Tom Sawyer and his friends play truant from school and set off for an island near their home town. Here they decide to play pirates but their game is interrupted when they witness a murder. Tom has to grow up very quickly and do the right thing.